The Protective Role Of Certain Antioxidants (Vitamins C And E And Omega-3 Oil) Against Aluminum Chloride Induced Biochemical Changes In Female Albino Rats (Rattus Rattus Norvegicus) - AL. Habbib, Omar A.M.; Gorgees, Najem S.; Hussein, Reyzan A. (Science Journal of University of Zakho, 2014)
The present study was undertaken to evaluate the protective effect of certain antioxidants such as Vitamins C, E and Omega-3 oil on Aluminum induced biochemical changes in the female albino rats. Sixty four female adult rats were divided randomly into two control: (control 1) 0 AlCl3 /Kg body weight (b.w.); (control 2) supplied orally with 0.2 ml/rat sun flower oil and six treated groups: AlCl3 (60 mg/kg b. w.) ; AlCl3 (60 mg/kg b. w.) plus 0.2ml/rat of 0.5% Acetic acid; AlCl3 (60 mg/kg b. w.) plus Vit.C (50 mg/kg); AlCl3 (60 mg/kg b. w.) plus Vit.E (100 mg/kg); AlCl3 (60 mg/kg b. w.) plus 0.2 ml/rat of 5% Omega-3 and AlCl3 (60 mg/kg b. w.) plus Vit.C (50 mg/kg) plus Vit.E (100 mg/kg) plus 0.2ml/rat of 5% Omega-3 ) respectively. Rats were orally administered their respective doses every other day for 35 days. At the end of the experiments, body weights were recorded and blood samples were collected for biochemical tests. Rats treated with aluminum chloride in the presence or absence of acetic acid showed significant decreases in the rate of body weight gain as compared with the control. Antioxidants (Vitamins C, E and omega-3) along with aluminum chloride produced protective effects as the rate of body weight gain approximately was more or less similar to the normal values of the control.The rats treated with AlCl3 (in the presence or absence of acetic acid ) showed a significant increase in Alanine aminotransaminase (ALT), Aspartate aminotransaminase (AST), Urea and Creatinine and a significant decrease in serum albumin and total protein as compared with the control. The administration of antioxidants (Vit C, E and Omega-3 oil) along with AlCl3 showed protective effects on liver and kidney since ALT,AST,Urea,Creatinine, albumin and total protein were tending to return towards their normal levels of control. So, the present study showed that Vit C, E and Omega-3 oil can be effective in the protection of aluminum-induced toxicity